EFFECTIVITY OF BIOACCUMULATION AND TRANSLOCATION OF HEAVY METALS (CD, ZN, AND PB) IN AVICENNIA MARINA GROWING AT WONOREJO MANGROVE ECOSYSTEM, EAST SURABAYA - Sari, Syarifah Hikmah Julinda; Yona, Defri; Vidayanti, Viky; Ramadhan, Firman (Journal of Environmental Engineering and Sustainable Technology, 2023)
Avicennia marina is a species of mangrove that has been studied extensively for its capability to uptake and accumulate heavy metals. Since Avicennia marina was found in the Wonorejo Mangrove ecosystem, which confirmed received anthropogenic inputs from Surabaya as the second largest city in Indonesia, the effectivity of bioaccumulation and translocation metals Cd, Zn, and Pb was studied. The sediments, roots, stems and leaves of Avicennia marina were collected in three sites in Wonorejo Mangrove Ecosystem, East Surabaya. The measurement of Cd, Zn and Pb was conducted by ICP-MS. To assess the effectiveness of accumulation and translocation capability, Bioconcentration Factor (BCF) and Translocation Factor (TF) were calculated. The results showed that the distribution of heavy metals Cd and Pb in the organs of the mangrove Avicennia marina exhibited distinct patterns. Although both of them are considered as non-essential elements, Cd tends to distribute evenly until leaves parts, while Pb tends to retain in the roots. In the case of Zn, as an essential element, the uptake was more intense compared to non-essential elements and mobilized until the leaves parts. Interestingly, once all metals reach the stem, they might transfer to the leaves as shown by TF values more than 1. Therefore, Avicennia marine has an effective defense mechanism in the presence of metals by regulating the accumulation and translocation of metals into detoxifying organs.